Secondary omental torsion. (28th February 2012) - Sable, Shailesh; Gandhi, Vidhyachandra; Nagral, Sanjay; Nagral, Aabha
Abstract : A middle-aged-woman presented with symptoms and signs of acute abdomen. Clinically a suspicion of acute appendicitis was raised, although the abdominal x-ray and ultrasound were normal. She was managed conservatively, which she failed to respond. In the view of persisting pain, a contrast enhanced CT (CECT) was done. CECT showed a whirling mass of fatty and fibrous tissue adherent to the anterior abdominal wall suggestive of omental torsion and the diagnosis was confirmed on laparotomy and she underwent excision of the ischaemic omentum. Omental torsion though rare, should be included in the differential diagnosis of acute abdomen. High index of suspicion is required to diagnose this entity. CECT abdomen shows the classical finding of fatty mass with whirling pattern. It is seldom considered in the differential diagnosis preoperatively based on clinical findings and the diagnosis is only established during the surgical procedure.